Analisis Pengaruh Faktor Sosial Ekonomi Terhadap Akses Sanitasi Layak di Indonesia Tahun 2021 - Widyastuti, Dyah; Jamaluddin, Halim Nur; Arisanti, Rohimma; Kartiasih, Fitri (Seminar Nasional Official Statistics, 2023)
Access to sanitation is a fundamental component of health. Poor sanitation can reduce human welfare and hinder a country's socio-economic development. Therefore, access to adequate and equitable sanitation for all is a target to be achieved by 2030. This study aims to analyze the influence of socioeconomic factors on access to proper sanitation in Indonesia in 2021. The method used includes descriptive analysis in the form of graphs and data center sizes as well as inferential analysis with multiple linear regression. The results showed that the level of completion of high school and owning a latrine significantly increased access to proper sanitation. Conversely, the share of food expenditure significantly reduces access to proper sanitation. The government must prioritize sustainable education by expanding scholarship programs and also boosting financial support for the construction of sanitation facilities. To raise public awareness, there has to be more socialization and teaching about the value of good sanitation.